Development of a strategic plan of a construction organization - A.М. Tkachenko; Ye.L. Malyshev (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The development of a strategic plan is an important stage for any construction organization focused on successful development. The article describes the key aspects of developing a strategic plan, including analyzing the internal and external environment, defining the organization's mission, vision, and goals, as well as strategic priorities. Particular attention is paid to the definition of competitive advantages, risks and opportunities, as well as mechanisms for monitoring and evaluating the implementation of the strategic plan. The article examines theoretical and practical issues of strategic management as a modern direction of enterprise development. The theoretical and practical aspects of the formation and implementation of a strategic set of construction enterprises, taking into account the peculiarities of their industry, are considered. The performed analysis made it possible to generalize the methodological principles of creating a strategic set for construction enterprises, including its essence, components and procedural aspects. The article proposes to consider the strategic set as a hierarchical system of interconnected strategies of various levels and types, developed by the enterprise during a certain time period, taking into account the peculiarities of their functioning, potential and promising directions of development. The strategic orientation and positioning of the enterprise in the external environment is also determined based on the achievement of strategic goals. The features, structure of strategic management and the sequence of its main tasks in the management of the enterprise in the construction industry are characterized. The theoretical and practical aspects of strategic management as a modern direction of enterprise development are studied. Features, structure and sequence of the main tasks of strategic management in the context of management of enterprises in the construction industry are described. Criteria for assessing the competitiveness of a construction company have been developed, factors affecting the formation of its competitive advantages have been determined, and organizational measures have been proposed to increase the level of its competitiveness. Issues of internal management, resources, communication and involvement of interested parties are analyzed. The importance of strategic planning for the successful functioning of a construction organization in modern market conditions is revealed.